2001
DOI: 10.1002/1529-0131(200103)44:3<618::aid-anr110>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The Fcγ receptor IIIA‐158F allele is a major risk factor for the development of lupus nephritis among Caucasians but not non‐Caucasians

Abstract: Objective To determine whether inheritance of Fcγ receptor (FcγR) alleles conferring lower affinity for IgG binding increases the risk of developing lupus nephritis. Methods We compared the frequency of low‐affinity alleles of two FcγR polymorphisms (FcγRIIA and FcγRIIIA) among 235 patients with systemic lupus erythematosus (SLE) and proven nephritis (nephritis patients) and among 352 SLE patients with no evidence of renal disease (non‐nephritis control subjects). The ethnic distribution of patients in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…Surprisingly, we found no trend of association in European Americans, despite our population size. One study did show such an association (), and the basis for that finding may lie in the allele frequencies found in the control group, which were different from those found in our study and other studies ().…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, we found no trend of association in European Americans, despite our population size. One study did show such an association (), and the basis for that finding may lie in the allele frequencies found in the control group, which were different from those found in our study and other studies ().…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to the FCGR2B ‐232I/T polymorphism, the FCGR3A ‐176V/F polymorphism was also significantly associated with susceptibility to SLE in Japanese patients in this study, thus replicating previous observations in different populations by several groups (36–40). The Lathrop‐type analysis suggested that the association of FCGR3A ‐176F is perhaps weaker than that of FCGR2B , apart from a genotypic difference that stems from slight deviations from Hardy‐Weinberg equilibrium in the control population.…”
Section: Discussionsupporting
confidence: 90%
“…Characteristics of eligible studies. Twenty‐eight comparisons from 20 studies addressing the relationship between FcγRIIa‐R/H131 and susceptibility to SLE and/or the development of lupus nephritis were identified (4–19, 30–33). Three reports (5, 16, 30) were excluded because of extensive overlapping with other included publications.…”
Section: Resultsmentioning
confidence: 99%